Neglected trauma-induced testicular torsion: Clinical, sonographic, and surgical correlation in a 13-year-old adolescent - Manar Ezzahi, MD; Sara El Malih, MD; Zaid Ennasery, MD; Naoufal Boumahdi, MD; Amal Akammar, PhD; Nizar El Bouardi, PhD; Meriem Haloua, PhD; Badreeddine Alami, PhD; Moulay Youssef Alaoui Lamrani, PhD; Mustapha Maaroufi, PhD; Youssef Bouabdallah, PhD; Meryem Boubbou, PhD (Radiology Case Reports, 2023)
Post-traumatic testicular torsion is a rare condition, accounting for approximately 4%-8% of all reported cases of testicular torsion in the literature. Prompt clinical suspicion and intervention are crucial; as testicular torsion is considered a medical and surgical emergency that may lead to testicular necrosis. Ultrasound imaging plays an important role in assessing the integrity of the traumatized scrotum and facilitating early detection of associated testicular torsion. In this case report, we present a neglected post-traumatic testicular torsion in a 13-year-old child that led to orchiectomy.